Prospective evaluation of neuromediator dynamics in castration-resistant prostate cancer patients during docetaxel - Hardenberg, Jost von; Schwartz, Maike; Weiß, Christel (Anticancer research, 2017)
Aim: Aim of the study was to detect small cell/neuroendocrine (SCNC) transformation in metastatic castration-resistant prostate cancer (mCRPC) that is a challenging procedure. We investigated the role of neuromediator dynamics as potential evidence of SCNC in patients undergoing docetaxel therapy. Patients and Methods: A multi-institutional, prospective observational study was conducted. Patients undergoing docetaxel treatment were included. Chromogranin A (CGA), neuron-specific enolase (NSE), and pro-gastrin releasing peptide (Pro-GRP) were sequentially evaluated at predefined time points. Outcome measures were overall survival (OS), progression-free survival (PFS) and PSA nadir. Results: Fifty-two patients were included. A general rise in CGA levels was observed. Patients with a high CGA rise (100%ULN: CGA ≥98.1ng/ml) between the 1st and 3rd cycle trended towards a decreased OS (p=0.0649) and showed a decreased PFS (p=0.0369). In multivariate analysis, continuous CGA rise correlated with PFS (p=0.0553; HR 1.136), but was not an independent predictor of OS. Conclusion: Patients with an early high CGA rise may demonstrate a subgroup with poor outcome due to underlying SCNC transformation. Monitoring of CGA appears to be an option worth considering.
Gesehen am 08.10.2018